Moonrise kingdom [videorecording (DVD)] - Anderson, Wes, 1969-; Willis, Bruce, 1955-; Norton, Edward; Murray, Bill, 1950 September 21-; Desplat, Alexandre (Focus Features, 2012)
Set on an island off the coast of New England in the summer of 1965, tells the story of two twelve-year-olds who fall in love, make a secret pact, and run away together into the wilderness. As various authorities try to hunt them down, a violent storm is brewing off-shore, and the peaceful island community is turned upside down in more ways than anyone can handle.